KEGEL'S EXERCISE DECREASE URINARY INCONTINENCE FOR POSTPARTUM MOTHER - Ni Ketut Alit Armini; Esti Yunitasari; Masadah Masadah (Universitas Airlangga, 2017)
Introduction: Trauma to the uretra and bladder may occur during the birth process when the infant passes through the pelvis. About 40% of women face urinary incontinence after childbirth. The aimed this study was to analyze the effect of keagle exercise to descent of urinary incontinence postpartum. Method: This study was used a quasy experimental sampling design. The population was all the mother after childbirth which has urinary incontinence. There were 14 respondents who met to the inclusion criteria. The independent variable was keagle exercise and the dependent variable was descent of urinary incontinence postpartum. Data were taken by structured interview with questionare and observation then analyzed by using Wilcoxon Signed Rank Test and Mann Whitney U Test with significance level of α≤0.05. Result: The result showed that after the application of keagle exercise, 100% of experimental group was had descent of urinary incontinence with Wilcoxon Signed Rank Test p=0.016 for capacity to urine preserve and p=0.020 for urine frequency in twenty four hours, then with Mann Whitney U Test p=0.026. Discussion: It can be concluded that keagle exercise has an effect to descent urinary incontinence postpartum. It is recommended to provide keagle exercise to mother after childbirth during hospitalize and further studies are recomended to find the difference of capacity to urine preserve and the frequency to urinate in twenty four hours prior to keagle exercise.